Professores iniciantes na educação infantil: desafios e possibilidades de enfrentamento em uma rede municipal de ensino - Silva, Silvana Saraid da (2021)
With a qualitative approach, this research had as purpose to investigate which challenges are met by beginning teachers in their teaching initiation, who deal with children from three to six years old in child education, and also to identify the possibilities they afford in order to face such issues. From the main objective, the following specific objectives were unfolded: to know how the entrance of beginning teachers takes place in the child education of the researched municipal network; to identify the challenges and obstacles faced during the start of the teaching in child education, to analyze the teacher’s perception on support possibilities in the start of the teaching and to discuss with the beginning teachers the challenges’ facing possibilities. The accomplishment of the research is justified by the understanding, from the literature review performed in this work, that there are few studies addressing this theme in this teaching modality. The theoretical frame selected to ground the research is composed by conceptions from Marcelo Garcia (2010); Vaillant and Marcelo (2012); and Flores (2004), who address the subject of the teacher’s professional development in the early career. Other contributions such as Campos’ (2006; 2008) and BNCC’s (2017) provided the perspective on the studied educational segment. The subjects of the research were four teachers who work in child education, with less than five years in the teaching career. The data gathering took place through Discussion Group. For the analysis, the Prose Analysis methodology formulated by André (1983) was used. Among the results, stands out that the initial formation received by the beginners presents itself as insufficient toward the practice requirement for working with small children, as well as the contradictions between enthusiasm with teaching and discontentment with working conditions. The data indicated yet the collaboration between peers as the main strategy for career survival and the confrontation of the major challenges pointed out in the teaching initiation. Such results allow the conclusion that the challenges met by beginning teachers are plural and inherent to their educational reality, and many times they are surpassed through the support among peers